Patterns of linguistics features in private chats of social media account leading someone to be a victim of a cyber crime - Ajar Pradika Ananta Tur (University of Muhammadiyah Purwokerto, 2019)
Social media have grown up as something hallucinogenic. They offer millions of pleasures by having people’s fingertips to control through smart phones. People may interact to each other for various motivations and purposes without knowing who they are talking to in fact although they know the name of the interlocutor shown in the social media account. This leads to cybercrime because people often miss to validate it. This research would like to investigate why people close their eyes to verify the person they are talking to in the social media and how the interlocutors enable to ensure that they are the same person as in the speakers thought. By having descriptive qualitative method with interview as the major for collecting data, the research results some signposts. Addressing, tone, and spelling and punctuation are linguistics features that the doer of cybercrime must have as a key to crack the security without any violence. The doer copies how the way people having the account of social media to ensure the interlocutor through a private chat.